Adaptation of School Engagement Measurement-MacArthur (SEM) Indonesian Version in the Context of Distance Learning - Zanira, Dhiya; Cahyadi, Surya (Universitas Muhammadiyah Metro, 2021)
Student engagement greatly influences education, especially during Distance Learning (PJJ), such as during the covid-19 pandemic. To find out the student engagement of students undergoing PJJ, it is necessary to measure student engagement. A measuring tool that provides comprehensive and standardized information and is also widely adopted in several countries is the SEM-MacArthur measuring instrument. SEM-MacArthur is a measuring tool that measures student engagement based on student engagement theory from J. A. Fredricks & Paris (2005). Adaptation is carried out based on the guidelines for adaptation of measuring instruments from the International Test Commission (ITC), which includes a forward-backward translation process, followed by an expert review to test language and conceptual equivalence. The validation process tests content validity through the Content Validity Index (CVI) and constructs validity using Confirmatory Factor Analysis (CFA). The trial was conducted on 233 high school students in Bandung who were between grades X to XII with ages ranging from 14 to 18 years. Based on this trial process, it is known that each indicator, dimension, and construct meets all the criteria for Goodness of Fit (RMSEA < 0.08; CFI > 0.9). In addition, the value of Construct Reliability (CR) > 0.70 and CFA > 0.40 was also obtained. Thus, the Indonesian version of the SEM-MacArthur measuring instrument in the context of PJJ can be used as a valid and reliable measuring tool.Keywords: school engagement measurement-macarthur (sem); student engagement; distance learning (pjj)Student engagement memiliki pengaruh yang besar dalam dunia pendidikan khususnya saat Pembelajaran Jarak Jauh (PJJ) seperti saat pandemi covid-19 ini. Untuk mengetahui student engagement yang dimiliki oleh siswa yang sedang menjalani PJJ, perlu dilakukan sebuah pengukuran mengenai student engagement. Adapun sebuah alat ukur yang memberikan informasi secara komprehensif dan terstandarisasi dan juga banyak diadaptasi di beberapa negara adalah alat ukur SEM-MacArthur. SEM-MacArthur merupakan alat ukur yang mengukur student engagement yang berlandaskan teori student engagement dari J. A. Fredricks & Paris (2005). Adaptasi dilakukan berdasarkan pedoman adaptasi alat ukur dari International Test Commission (ITC), yang meliputi proses forward-backward translation, dilanjutkan dengan expert review untuk menguji ekuivalensi bahasa dan konseptual. Adapun proses validasi dilakukan dengan menguji validitas isi, melalui Content Validity Index (CVI), dan validitas konstruk, menggunakan Confirmatory Factor Analysis (CFA). Uji coba dilakukan kepada 233 ssiswa SMA di Kota Bandung yang berada antara kelas X hingga XII dengan usia berkisar antara 14 hingga 18 tahun. Berdasarkan proses uji coba ini, diketahui bahwa setiap indikator, dimensi, dan konstruk memenuhi semua kriteria Goodness of Fit (RMSEA < 0,08; CFI > 0,9). Di samping itu, diperoleh juga nilai Construct Reliability (CR) > 0,70 dan CFA > 0,40. Dengan demikian, alat ukur SEM-MacArthur versi Bahasa Indonesia konteks PJJ dapat digunakan sebagai alat ukur yang valid dan reliabel.Kata kunci: school engagement measurement-MacArthur (sem); student engagement; pembelajaran jarak jauh (pjj)